Skills for Europe's future : anticipating occupational skill needs - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
The present publication contains the contributions, the summary of the discussions in the working groups and the conclusions of the Agora conference "Skills for Europe's future" on 21-22 February 2008 in Thessaloniki. The main topic was the first pan-European forecast of occupational skill needs up to 2015 for EU-25, Norway and Switzerland, which was conducted by Cedefop with support of its expert network Skillsnet. Other objectives of the conference were to discuss the findings and future network plans with policy-makers, social partners, practitioners and all other relevant stakeholders. (BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; T 3 Forschungsmethoden; I 2.2 Europa; Qualifikationsbedarf; Früherkennung; Beschäftigungsentwicklung; Wirtschaftszweig; Fachkräftemangel; Demografischer Wandel; Prognose; Szenario; Europäische Union